The role of K(+) channels in the force recovery elicited by Na(+)-K(+) pump stimulation in Ba(2+)-paralysed rat skeletal muscle - Clausen, Torben (Blackwell Science Inc, 2000)
1. The present experiments were performed to assess the role of K(+) channels in hormonal stimulation of the Na(+)-K(+) pump and to determine the contribution of Na(+)-K(+) pumps to the recovery of excitability and contractility in depolarized skeletal muscle. 2. In soleus muscle, Ba(2+) (0.02 and 1 mm) was found to inhibit (42)K(+) efflux and (42)K(+) influx. Both in the absence and the presence of Ba(2+) (1 mm), salbutamol and calcitonin gene-related peptide (CGRP) induced a marked decrease in intracellular Na(+) and stimulation of (42)K(+) uptake. 3. In soleus muscles Ba(2+) (0.1 and 1.0 mm) decreased twitch and tetanic force. Subsequent stimulation of the Na(+)-K(+) pumps by salbutamol, CGRP or repeated electrical stimulation produced a highly significant restoration of force development, which was suppressed by ouabain, but not by glibenclamide. Also, in extensor digitorum longus muscles Ba(2+) (0.1 mm) produced a considerable force decline, which was partly restored by salbutamol and CGRP. 4. The area of compound action potentials (M-waves) elicited by indirect stimulation was decreased by Ba(2+) (0.1 mm). This was associated with a concomitant decrease in tetanic force and depolarization. Salbutamol, CGRP or repeated electrical stimulation all elicited marked recovery of M-wave area, force and membrane potential. All recordings showed close correlations between these three parameters. 5. The data add further support to the concept that due to its electrogenic nature and large transport capacity, the Na(+)-K(+) pump is a rapid and efficient mechanism for the maintenance of excitability in skeletal muscle, acting independently of Ba(2+)- or ATP-sensitive K(+) channel function.